Applying Skimming Strategy in Teaching Reading Descriptive Text - Vemby Ari Sandi (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
Reading is an important activity to enrich knowledge. However, it is considered as a difficult skill to learn. There are many students facing difficulties in comprehending the content of the reading text, including descriptive text. A strategy which can solve such problems is needed. Skimming strategy is the strategy which enable students to quickly find the main idea and relevant information of the text. Based on those reasons, the research questions are proposed as follows: (1) How can skimming strategy be implemented in teaching reading descriptive texts? and (2) How can the second year students’ reading comprehension ability be improved using skimming strategy? This study used two research methods. Those were qualitative and quantitative research design. They were collected to prove the implementation and the significant improvement by using skimming strategy. Both numeric information and the real observation were evaluated to gain clear and strong data. The researcher acted as the observer to see the process of teaching and learning descriptive texts in three stages. The results of the research showed that the teacher and students implemented four steps of skimming strategy, which are: (1) read the first several paragraph; (2) leave out material; (3) find the main ideas; (4) read fast. The t-test of this research was also calculated to see whether there was a significant difference between control and experimental class and the mean was also measured to see the students’ improvement score. The mean score of experimental class was better than the mean score of control class. However, the t-test result showed that there was no significant difference between experimental and control class.